3-O-tert-butyldimethylsilyl-2,2 ': 5,6-di-O-isopropylidene-2-C-hydroxymethyl-D-1,4-gluconolactone - Cowley, A; Fleet, G; Simone, M; Soengas, R (2004)
The C19H34O7Si was derived from the minor component of a Kiliani reaction on d-fructose. Its crystal structure has been determined in order to confirm its structure, and stereochemistry. The scaffolds provide efficient access to highly functionalized compounds containing non-linear carbon chains. The Kiliani reaction of d-fructose proceeds in good yield to give a mixture of the two diastereomers which cannot easily be separated. The direct treatment of the crude material produced the diacetonide as the major product, which crystallized easily.